1968
DOI: 10.1063/1.1656436
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Orientation and Lattice Parameters from Kossel Lines

Abstract: A Kossel x-ray diffraction pattern of a single crystal contains information concerning crystal orientation, structure, and lattice parameters. Procedures have been developed for determining orientations to within ±0.5°, identifying conics and calculating d spacings to within ±0.5%, and determining lattice parameters in any crystal system with errors as small as 10 ppm. Orientation and structure calculations can be made starting with position measurements taken directly from a Kossel pattern. Precision paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Pitsch and his coworkers (Ryder, H~ilbig & Pitsch, 1967, 1968 have shown that the minimum radius of curvature ofa Kossel line (hkl) which is the radius of curvature of the osculating circle at the apex of the conic, is given by the equation:…”
Section: (B) Radius Of Curvature Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pitsch and his coworkers (Ryder, H~ilbig & Pitsch, 1967, 1968 have shown that the minimum radius of curvature ofa Kossel line (hkl) which is the radius of curvature of the osculating circle at the apex of the conic, is given by the equation:…”
Section: (B) Radius Of Curvature Methodsmentioning
confidence: 99%
“…8"3. Heise's (1962a, b) method [For a systematic treatment of this method, see also Gielen, Yakowitz, Ganow & Ogilvie (1965) and Morris (1968)].…”
Section: Schwarzenbergermentioning
confidence: 99%
See 1 more Smart Citation
“…of Kassel Diffraction in SEM 81 Tixier and Wache (1970) near or exact Kosselline intersections 1 in 10 4 3 Lonsdale (1947) bracketing of Kossellines 3 2 Kossel (1936a, b) near tangency of Kossel lines 1 in 10 4 3 4 Mackay (1966) near tangency of Kossellines 1 in 10 4 3 1 Schwarzenberger (1959) near Kosselline intersections 4 in 10 4 3 1 Heise (1962) lens method 1 in 10 4 -2 x 10 4 3 4 Hanneman et al (1962) lens method 1 in 105 -2 x 10 4 3 2 Gielen et al (1965) lens method 3 4 Morris (1968) lens method 1 in 10 4 -2 x 10 4 3 4 Yakowit: (1973) lens method 1 in 10 4 -2 x 10 4 3 2…”
Section: Htstoncal Surveymentioning
confidence: 99%
“…of Kassel Diffraction in SEM 81 Schneider and Weik (1968) variable camera geometry 2 1 Fisher and Harris (1970) variable camera geometry 1 in 10 3 2 1 Morris (1968) conic fitting 1 in 200 2 conic fitting 1 Harris and Kirkham (1971) conic fitting 1 in 10 3 1 Kossel (1936a, b) comparison with prepared projection 4 Lonsdale (1947) comparison with prepared projection 4 Peters and Ogilvie (1965) stereographic proj ection 4 1 Mackay (1966) superposition of prepared charts 4 1 Ryder, Halbig and Pitsch (1967) radius of curvature 4 1 Rowlands and Bevis (1968) superposition of prepared charts 4 1 Harris and Kirkham (1971) conic fitting 1 Heise (1962) cylindrical film 2°4 1 Peters and Ogilvie (1965) stereographic projection 1-2°4 1 Bevis and Swindells (1967) Kossel line intersections 1.5°4 2 Ryder et al (1967) Kosselline intersections 0.15°4 Rowlands and Bevis (1968) superposition of prepared charts 0.5°4 1 Bevis et al (1970) conic fitting 1 Harris and Kirkham (1971) conic fitting 1 * From Biggin and In describing the essential elements of the patterns, Kossel (1936a) found it useful to construct an imaginary sphere of radius 2//L and centred at the origin of reciprocal space. For each permitted reflection, he drew a cone of semi-apex angle (90 -e B ) , whose axis joined the corresponding reciprocal lattice point with the origin.…”
Section: Htstoncal Surveymentioning
confidence: 99%